2020
DOI: 10.1515/jpm-2019-0422
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking and cannabis use during pregnancy and infant outcomes

Abstract: BackgroundOur aim was to determine the prevalence of tobacco smoking and e-cigarettes and cannabis use during pregnancy, whether these were influenced by ethnicity, and their relationship to perinatal outcomes.MethodsA study was carried out in 4465 infants whose mothers delivered during 2017 and 2018. Self-reported maternal smoking, e-cigarette and cannabis use at booking were recorded. Outcome measures were birthweight and head circumference z-scores and admission to the neonatal intensive care unit (NICU).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Additionally, we found a tendency for smaller length and head and chest circumferences in newborns from active smoking women compared to those from nonsmoking mothers. These findings are strongly supported by similar studies, where maternal active smoking was associated with a lower mean birth weight [14,25], smaller length and head circumference [1,2,33], and abnormal body proportions [18,30].…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, we found a tendency for smaller length and head and chest circumferences in newborns from active smoking women compared to those from nonsmoking mothers. These findings are strongly supported by similar studies, where maternal active smoking was associated with a lower mean birth weight [14,25], smaller length and head circumference [1,2,33], and abnormal body proportions [18,30].…”
Section: Discussionsupporting
confidence: 81%
“…Studies have found that natural delivery can generate a stress response, which is mainly stimulated by fetal birth canal pressure, hence leading to a series of endocrine alterations and promoting the production of neonatal immune factors to enhance immune function, providing more resistance for neonates than cesarean section. In addition, natural delivery can also promote postpartum milk secretion and improve the relationship between puerperae and fetuses [ 11 , 12 ]. The study found that taking health products containing TCM before delivery could invigorate the spleen and kidney, nourish blood, and prevent abortion, which had a significant effect on pregnant women with habitual abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Significant GR was detected in the infants from the smoking groups (NoDrugsSmoke, NoDrugsDrinkSmoke, MarDrinkSmoke, and All), with >25% of the MarDrinkSmoke group being affected. El Marroun et al [58] reported that marijuana use during pregnancy resulted in more pronounced GR than tobacco use, while Sturrock et al [59] also found that cigarette smoking was associated with a lower BWZ, but that women who both smoked and used marijuana during pregnancy had infants with a lower BWZ than those who used Maternal arm circumference differed significantly between any two groups when there was no overlap of letters above the vertical bars. Maternal age differed significantly between any two groups when there was no overlap of letters above the vertical bars.…”
Section: Fig 1 Gestational Age At Enrolment Compared Among Different ...mentioning
confidence: 99%